2021
DOI: 10.1177/03913988211051395
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound and the role of lung aeration score in patients with acute respiratory distress syndrome on extracorporeal membrane oxygenation

Abstract: Objective: This was a pilot study to determine the utility of daily lung ultrasound (LUS) in patients requiring veno-venous extracorporeal membrane oxygenation (VV-ECMO) for acute respiratory distress syndrome (ARDS). Design: This was a prospective, observational study. Setting: The study took place in the intensive care unit at Royal Papworth Hospital in Cambridge, UK. Participants: We recruited adult patients receiving VV-ECMO for ARDS. Interventions: All patients received a lung computed tomography (CT) sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Bedside pulmonary ultrasound has been established as an important tool for the evaluation of critically ill patients and has been proven to be helpful in the diagnosis of speci c pathological features, such as interstitial oedema, consolidation and pleural effusion [17]. In this retrospective study, dynamic pulmonary ultrasound monitoring was performed on 22 patients who received VA-ECMO treatment for shock.…”
Section: Discussionmentioning
confidence: 99%
“…Bedside pulmonary ultrasound has been established as an important tool for the evaluation of critically ill patients and has been proven to be helpful in the diagnosis of speci c pathological features, such as interstitial oedema, consolidation and pleural effusion [17]. In this retrospective study, dynamic pulmonary ultrasound monitoring was performed on 22 patients who received VA-ECMO treatment for shock.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study determining the utility of daily LUS in patients requiring veno-venous ECMO, for acute respiratory distress syndrome, reported that LUS correlated with CT and CXR findings. 1…”
Section: Discussionmentioning
confidence: 99%
“…Shred sign is visible where alveolar air has been replaced by fluid, giving the lung a tissue like appearance. 1,6 Air bronchograms appear as hyperechoic lines within a hypoechoic area, representing air trapped in small airways within consolidation. 1 As the assessment findings displayed persistent right lung collapse and consolidation physiotherapy treatment was completed.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung ultrasound can be used to guide the setting of mechanical ventilation in ARDS patients and assess bedside lung recruitment [ 34 ]. Changes in the lung ultrasound score correlated with PEEP-induced increases in end-expiratory lung volume in a series of ARDS patients receiving conventional mechanical ventilation [ 35 ] and also correlated significantly with computed tomography (CT) scan data in a series of 18 patients receiving ECMO [ 36 ].…”
Section: How To Set the Optimal Peep On Ecmo?mentioning
confidence: 99%